Drivers of Ice Algal Bloom Variability Between 1980 and 2015 in the Chukchi Sea. Issue 10 (2nd October 2018) - Selz, Virginia; Saenz, Benjamin T.; van Dijken, Gert L.; Arrigo, Kevin R.
Abstract: Sea ice provides an important habitat for the ice algae that fuel upper trophic levels in early spring, prior to phytoplankton bloom development. In the Chukchi Sea, the ice environment has experienced large‐scale changes in snow cover, ice thickness and extent, and timing of ice advance and retreat. Using a 1‐D coupled physical‐biological ice‐ecosystem model and observed distributions of sea ice, we investigated how changing ice conditions may have impacted ice algal bloom dynamics for the central Chukchi Sea between 1980 and 2015. Model results suggest that over this 35‐year time period, annual ice algal net primary production (NPP) decreased by 22%. Modeled snow and ice melt, as well as satellite‐derived ice retreat, occurred progressively earlier in the spring from 1980 to 2015, even though modeled ice and snow thicknesses showed no temporal trends. Over time, ice algal blooms ended earlier in spring due to earlier onset of ice melt and ice retreat. Results suggest that the length of the ice season sets the upper bound on annual ice algal NPP, with late melt years corresponding to highest NPP. Linear regression results suggest that within early versus late melt year groupings, snow plays a secondary, yet important role in determining annual ice algal NPP. As sea ice thins and melts earlier in spring, future snow dynamics will be an important factor determining the onset of the ice algal bloom and thus the duration of the bloom in an early melt, shortened ice season scenario. Plain Language Summary: Sea ice provides an important habitat for the ice algae that fuel upper trophic levels in early spring, prior to phytoplankton bloom development. In the Chukchi Sea, the ice environment has experienced large‐scale changes in snow cover, ice thickness and extent, and timing of ice advance and retreat. Using a modeling study that simulated the sea ice environment and sea ice ecosystem, we investigated how changing ice conditions may have impacted ice algal bloom dynamics for the central Chukchi Sea between 1980 and 2015. Modeling results suggest that ice algal blooms end earlier in spring due to earlier onset of ice melt and ice retreat. Earlier bloom termination leads to declines in ice algal production between 1980 and 2015. Key Points: Ice algal production has decreased 22% in the central Chukchi Sea from 1980 to 2015 Ice season duration sets the upper limit on annual ice algal production Snow thickness can compensate for or amplify the impact of a shortening ice season